LOBULAR CAPILLARY HEMANGIOMA OF ORAL CAVITY: A CASE REPORT - Venkateshwar, Dr. Gokul; Dr. Riya; Sharma, Dr. Shivani; Raut, Dr. Tejas; Padavala, Dr. Vamshika; Kshirsagar, Dr. Vaishnavi (South Eastern European Journal of Public Health, 2025)
The case report highlights an intraoral presentation of a lobular capillary hemangioma. The extensive growth of the tumor, causing significant complications such as sudden excessive bleeding, underscores the often insidious nature of LCHs. The patient underwent surgical excision of the tumor. Histopathology confirmed lobular capillary hemangioma. The one-month follow-up demonstrated complete resolution of symptoms and uneventful healing, reaffirming the efficacy of the chosen treatment approach. Comprehensive evaluation and a multidisciplinary approach were crucial for successful management, emphasizing the need for awareness of this entity among oral and maxillofacial surgeons.